RELIGIOUS AND SOCIAL-PSYCHOLOGICAL FEATURES OF ADOPTING MANAGEMENT DECISIONS AMONG EXECUTIVES - Nazarov Azamat Sottarovich (American Journals Publishing, 2024)
This article examines religious and socio-psychological factors that influence the process of making management decisions among executives. Various aspects, such as worldview, moral attitudes and influence group, as well as their significance for management effectiveness are analyzed.
Keywords: Decision making, management decisions, conscious choice, determinism, indeterminism, management activity, management decision, extreme factors, negative functional states.